Pendampingan Strategi Pemasaran Digital bagi UMKM “DnD Donat” di Kecamatan Dlanggu, Kabupaten Mojokerto sebagai Upaya Peningkatan Daya Saing - M.Syamsul Hidayat; Eny Setyariningsih (Lembaga Pengembangan Kinerja Dosen, 2025)
One of the digital marketing strategies commonly used by companies and Micro, Small, and Medium Enterprises (MSMEs) to introduce their products and achieve optimal profits is through the use of social media (Hidayat et al., 2022). The rapid development of information technology, particularly the internet and social media, has significantly changed consumer behavior and the way businesses operate. Digital marketing provides strategic opportunities for business actors, including lower promotional costs, increased brand awareness, and the potential to boost sales (Dwivedi et al., 2020). However, many MSMEs have not yet fully utilized digital marketing strategies through social media. The lack of digital literacy and limited understanding of effective marketing strategies remain major challenges in business development. To address these issues, a community service team from the Faculty of Economics, Universitas Islam Majapahit, implemented a mentoring program for the MSME “DnD Donat” located in Dlanggu District, Mojokerto Regency. The objective of this program was to provide the partner with the knowledge and practical skills necessary to design and implement an effective digital marketing strategy using social media as the primary promotional channel. Through this mentoring activity, the partner received education on the fundamentals of digital marketing, how to create engaging promotional content, and how to effectively use social media platforms such as Instagram and WhatsApp Business. The results of the program showed that the partner gained an understanding of digital marketing strategies and began to implement them in their business activities. The positive impact of the program was reflected in a noticeable increase in both sales volume and income over a specific period following the implementation of the new marketing approach. This program is expected to serve as a model for developing digital capabilities among other MSMEs and to support the broader digital transformation in the micro and small business sector in a sustainable manner.